Proposal of a Sizing Algorithm for an Optimal Design of DC/DC Converters Used in Photovoltaic Conversion - Amrouayache Mohamed (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
The solar energy is converted to electrical energy by means of semiconductor materials called solar panels. However, the conversion efficiency is low, and hence the need to harvest the maximum power to optimize the photovoltaic conversion, for that the MPPT (Maximum Power Point Tracker) technique is used to maximize the power delivered by the solar panel (PV); this power is very fluctuating because it depends on the lightning and the temperature, the maximum power point is acquired by a DC / DC converter connected to the closed loop MPPT algorithm. The design of the circuit (the closed loop) must be robust in the face of changes in operating points caused by variations in meteorological conditions (temperature and lighting) and must always maintain certain performances such as stability, a fast and well-damped transient system, precision. In this paper, we presented a study of closed loop, for that, we established the average small signal model of the different topologies of the converters (boost; buck, buck-boost) to have a linear model. A comparative study between the three topologies has been established, to make an optimal choice of the circuit parameters.